Vitamin E succinate mediated apoptosis by juxtaposing endoplasmic reticulum and mitochondria - Ray, Manobendro Nath; Kiyofuji, Michiko; Ozono, Mizune; Kogure, Kentaro (Biochimica et biophysica acta. General subjects, 2023)
Vitamin E succinate (VES) is an esterified form of natural α-tocopherol, has turned out to be novel anticancer agent. However, its anticancer mechanisms have not been illustrated. Previously, we reported VES mediated Ca2+ release from the endoplasmic reticulum (ER) causes mitochondrial Ca2+ overload, leading to mitochondrial depolarization and apoptosis. Here, we elucidated the mechanism of VES-induced Ca2+ transfer from ER to mitochondria by investigating the role of VES in ER-mitochondria contact formation. Transmission electron microscopic observation confirms VES mediated ER-mitochondria contact while fluorescence microscopic analysis revealed that VES increased mitochondria-associated ER membrane (MAM) formation. Pre-treatment with the inositol 1,4,5-triphosphate receptor (IP3R) antagonist 2-aminoethyl diphenylborinate (2-APB) decreased VES-induced MAM formation, suggesting the involvement of VES-induced Ca2+ efflux from ER in MAM formation. The ER IP3R receptor is known to interact with voltage-dependent anion channels (VDAC) via the chaperone glucose-regulated protein 75 kDa (GRP75) to bring ER and mitochondria nearby. Although we revealed that VES treatment does not affect GRP75 protein level, it increases GRP75 localization in the MAM. In addition, the inhibition of Ca2+ release from ER by 2-APB decreases GRP75 localization in the MAM, suggesting the possibility of Ca2+-induced conformational change of GRP75 that promotes formation of the IP3R-GRP75-VDAC complex and thereby encourages MAM formation. This study identifies the mechanism of VES-induced enhanced Ca2+ transfer from ER to mitochondria, which causes mitochondrial Ca2+ overload leading to apoptosis.Vitamin E succinate (VES) is an esterified form of natural α-tocopherol, has turned out to be novel anticancer agent. However, its anticancer mechanisms have not been illustrated. Previously, we reported VES mediated Ca2+ release from the endoplasmic reticulum (ER) causes mitochondrial Ca2+ overload, leading to mitochondrial depolarization and apoptosis. Here, we elucidated the mechanism of VES-induced Ca2+ transfer from ER to mitochondria by investigating the role of VES in ER-mitochondria contact formation. Transmission electron microscopic observation confirms VES mediated ER-mitochondria contact while fluorescence microscopic analysis revealed that VES increased mitochondria-associated ER membrane (MAM) formation. Pre-treatment with the inositol 1,4,5-triphosphate receptor (IP3R) antagonist 2-aminoethyl diphenylborinate (2-APB) decreased VES-induced MAM formation, suggesting the involvement of VES-induced Ca2+ efflux from ER in MAM formation. The ER IP3R receptor is known to interact with voltage-dependent anion channels (VDAC) via the chaperone glucose-regulated protein 75 kDa (GRP75) to bring ER and mitochondria nearby. Although we revealed that VES treatment does not affect GRP75 protein level, it increases GRP75 localization in the MAM. In addition, the inhibition of Ca2+ release from ER by 2-APB decreases GRP75 localization in the MAM, suggesting the possibility of Ca2+-induced conformational change of GRP75 that promotes formation of the IP3R-GRP75-VDAC complex and thereby encourages MAM formation. This study identifies the mechanism of VES-induced enhanced Ca2+ transfer from ER to mitochondria, which causes mitochondrial Ca2+ overload leading to apoptosis.